2006
DOI: 10.1097/01.mnh.0000232880.58340.0c
|View full text |Cite
|
Sign up to set email alerts
|

Bone disease in idiopathic hypercalciuria

Abstract: Whether hypercalciuria is the result of a primary bone disorder, a consequence of a persisting negative calcium balance or a combination of both still remains to be determined. Nevertheless, bone status must be evaluated and followed up in patients with idiopathic hypercalciuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 83 publications
4
51
0
1
Order By: Relevance
“…As expected and in agreement with previous reports, the three treatments induced a significant reduction in 24-hour urinary calcium excretion [Heilberg and Weisinger, 2006;Ceylan et al 2005;Weisinger et al 1997Weisinger et al , 1998]. Interestingly, the authors found that women in the combination therapy group (alendronate weekly plus indapamide daily) experienced the highest reduction in urinary calcium excretion, resulting in an additional effect of the two drugs.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…As expected and in agreement with previous reports, the three treatments induced a significant reduction in 24-hour urinary calcium excretion [Heilberg and Weisinger, 2006;Ceylan et al 2005;Weisinger et al 1997Weisinger et al , 1998]. Interestingly, the authors found that women in the combination therapy group (alendronate weekly plus indapamide daily) experienced the highest reduction in urinary calcium excretion, resulting in an additional effect of the two drugs.…”
supporting
confidence: 80%
“…Studies on humans, however, suggest that whereas some patients have a single specific defect resulting in hypercalciuria, most subjects do not have a specific site of mineral ion transport dysregulation. Therefore, IHC seems to be a systemic disorder of mineral ion homeostasis resulting from the interaction of different mechanisms [Heilberg and Weisinger, 2006].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although hypercalciuria and bone-mass loss are classic features of primary hyperparathyroidism, there is also evidence that the prevalence of osteopenia is statistically increased in lithiasic patients with idiopathic hypercalciuria in comparison with normocalciuric patients (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased bone mineral density (BMD) is commonly encountered in IH patients (23), and an increased prevalence of bone fractures has been reported for nephrolithiasis patients (24,25). GHS rats also exhibited reduced BMD and more brittle and fracture-prone bones (26) because of lower trabecular volume and mineralized volume and thickness.…”
Section: Discussionmentioning
confidence: 99%